Oxidative release of nitrite from 2-nitrotoluene by a three-component enzyme system from Pseudomonas sp. strain JS42. - An, D (1994)
Pseudomonas sp. strain JS42 utilizes 2-nitrotoluene (2NT) as the sole source of carbon and energy for growth. Intact cells catalyze the oxidation of 2NT to 3-methylcatechol and nitrite in a reaction that requires molecular oxygen. Cell extracts oxidized 2NT to 3-methylcatechol and nitrite in the presence of NAD(P)H and ferrous iron. Ion-exchange chromatography yielded three protein fractions (A, B, and C) which were all required for the oxidation of 2NT to 3-methylcatechol and nitrite. Component B (reductase2NT) catalyzed a NAD(P)H-dependent reduction of cytochrome c. Solutions of component A (ISP2NT) were brown and showed absorption maxima at 458 and 324 nm. Two major bands with M(r)s 52,500 and 28,000 were observed when ISP2NT was analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Component C could be replaced by ferredoxin NAP from the Pseudomonas putida NCIB 9816-4 naphthalene dioxygenase system and was given the designation ferredoxin2NT. Experiments with 18O2 showed that both oxygen atoms were added to the aromatic ring of 2NT to yield 3-methylcatechol. The enzyme is a new multicomponent enzyme system which we have designated 2NT 2,3-dioxygenase.